High-Temperature Radical Copolymerization of Dibutyl Itaconate With N-Butyl Acrylate, Methyl Methacrylate and Styrene (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
The homopolymerization of itaconates results in relatively short polymer chains and low monomer conversions. To study whether copolymerization provides a more favorable result, dibutyl itaconate was copolymerized with n-butyl acrylate, methyl methacrylate and styrene. In addition to representing the most commercially preferred monomer families, these co-monomers were also chosen due to the differences in the secondary reactions that occur during polymerization at elevated temperatures. Experiments were conducted under semi-batch operating conditions at 110 °C with equal molar ratios of the co-monomer to dibutyl itaconate to enable direct comparison of the results. The impact of varying monomer compositions on polymer molecular mass distributions and polymerization rates was studied, with samples analysed using size exclusion chromatography and high-performance liquid chromatography.